2009
DOI: 10.1016/j.scriptamat.2009.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Monoclinic B-phase erbium sesquioxide (Er2O3) thin films by filtered cathodic arc deposition

Abstract: Er 2 O 3 sesquioxide thin films in the uncommon, monoclinic phase were produced for the first time by filtered cathodic arc deposition on Eurofer steel substrates. This was achieved by applying a sample bias of -250 V and deposition temperatures ≤400 °C. XRD texture analysis revealed a strong preferred orientation of the B-phase crystallites. Deposition at 600 °C without bias voltage resulted in thin films showing the regular cubic phase. A dense, columnar structure was found for both phases by scanning transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The capacitance value in the strong accumulation region was measured as 7.52 × 10 −10 F, and the dielectric constant was calculated as 12.22, the value of which is given in the range of 9-14 in the literature [27], [32], [35]. …”
Section: A Description Of the Samplesmentioning
confidence: 99%
“…The capacitance value in the strong accumulation region was measured as 7.52 × 10 −10 F, and the dielectric constant was calculated as 12.22, the value of which is given in the range of 9-14 in the literature [27], [32], [35]. …”
Section: A Description Of the Samplesmentioning
confidence: 99%
“…Studies have shown that monoclinic yttrium oxide films have been prepared by Chang et al by MBE [16], by Lacroix through ion beam deposition [20] and by Gaboriaud with ion irradiation [22]. Similar results have also been observed for erbium oxide [23,24]. Indeed, monoclinic phase is a thermodynamically metastable phase, whose formation deviates from equilibrium.…”
Section: Introductionmentioning
confidence: 53%
“…It was shown that the introduction of compressive stress by ion beam assisted deposition causes formation of the metastable cubic BN and monoclinic Gd 2 O 3 phase. The stress-induced phase transition is also well-documented for other systems, like Er 2 O 3 (Adelhelm et al, 2009) and partially stabilized zirconia (Piascik et al, 2007). In addition, intensive theoretical and experimental studies showed that the external pressure induces the phase transition in GaN (Muoz and Kunc, 1991;Perlin et al, 1992;Yao and Klug, 2013).…”
Section: Discussionmentioning
confidence: 76%